CRITICAL DISCOURSE ANALYSIS (CDA) OF SINDO NEWSPAPER (CDA A MODEL OF VAN DIJK) - Dewi Yana (CAHAYA PENDIDIKAN, 2015)
This study aims at describing the text analysis, social cognition, social context, and ideology of sindo newspaper of  Wednesday December 11th 2013 edition.. This study uses Critical Discourse Analysis method  with  a Teun A Van Dijk  approach model.  The data were in the form of news entitled “Putusan Luthfi Hasan Diharapkan Jadi Efek Jera”. The data were analyzed with integrating the third dimension of Teun A Van Djik Discoure model in the unity analysis, they were text, social cognition, and social context. The results found that the Sindo Newspaper supported the work of the Corruption Eradication Commission (KPK) and the presiding judge of Corruption Court (Tipikor). The news in the edition of Wednesday, December 11th, 2013 “the  ideology of Sindo Newspaper practically used  to build the image of KPK and TIPIKOR to be more better in the society